2010
DOI: 10.1667/rr1895.1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Bystander Response in Human Glioma Cells using High-Energy Electrons: A Role for TGF-β1

Abstract: We examined bystander cell death produced in T98G cells by exposure to irradiated cell conditioned medium (ICCM) produced by high-energy 20 MeV electrons at a dose rate of 10 Gy min(-1) and doses up to 20 Gy. ICCM induced a bystander response in T98G glioma cells, reducing recipient cell survival by more than 25% below controls at 5 and 10 Gy. Higher doses increased survival to near control levels. ICCM was analyzed for the presence of transforming growth factor alpha (TGF-alpha) and transforming growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 61 publications
1
41
0
Order By: Relevance
“…Cells located as far as 1 mm in 3D cultured tissue 2 and 7.5 mm in 2D cultured cells 3 from the directly irradiated cells were shown to display cytotoxic and genotoxic effects that were believed to be the consequences of RIBE. It was proposed that both gap junction intercellular communication (GJIC) 4 and soluble factors such as reactive oxygen species (ROS), 5 nitric oxide (NO), 6 calcium fluxes, 7 and cytokines such as interleukin-8 (IL-8), 8 tumor necrosis factor-a (TNF-a), 9 and transforming growth factor-b1 (TGF-b1) [10][11][12] generated by directly irradiated cells participate in the bystander effects. However, most of the studies were focused on signals exiting irradiated cells and likely detected by bystander cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells located as far as 1 mm in 3D cultured tissue 2 and 7.5 mm in 2D cultured cells 3 from the directly irradiated cells were shown to display cytotoxic and genotoxic effects that were believed to be the consequences of RIBE. It was proposed that both gap junction intercellular communication (GJIC) 4 and soluble factors such as reactive oxygen species (ROS), 5 nitric oxide (NO), 6 calcium fluxes, 7 and cytokines such as interleukin-8 (IL-8), 8 tumor necrosis factor-a (TNF-a), 9 and transforming growth factor-b1 (TGF-b1) [10][11][12] generated by directly irradiated cells participate in the bystander effects. However, most of the studies were focused on signals exiting irradiated cells and likely detected by bystander cells.…”
Section: Introductionmentioning
confidence: 99%
“…19 Since the observation that TGF-b1 was increased in a dose-dependent manner in irradiated rat liver, 20 multiple studies have demonstrated the involvement of TGF-b1 in direct radiation responses [21][22][23][24][25][26][27][28] and as an important mediator in RIBE. [10][11][12] It was suggested that TGF-b1 is induced by radiation at both transcriptional 23 and post-transcriptional levels. 29 However, the role of miRNAs in TGF-b1-mediated responses toward radiation is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of TGF-β1 induces reactive oxygen species and micronucleus in fibroblasts (shao et al 2008). Interestingly, TGF-β1 also mediates the bystander cell death in T98G glioma cells induced by high-energy 20 Mev electrons-irradiated cell-conditioned medium (Gow et al 2010). There is a significant increase in TGF-β1 secretion by endothelial cells in the stem cell niche after IR (Pineda et al 2013).…”
Section: Tgf-βmentioning
confidence: 99%
“…2012), and growth factors (Gow et al . 2010), as well as by gap junction intercellular communication (Azzam et al 2001, Shao et al 2003b, 2006, Autsavapromporn et al 2013).…”
Section: Introductionmentioning
confidence: 99%